Trends in Augmented Reality and Virtual Reality Studies in Sports Education: Bibliometric Analysis of the Scopus Database for 2019-2024 - Andry Akhiruyanto; Dewangga Yudhistira (OVS LLC, 2024)
Objective. The objective of this study was to conduct a bibliometric analysis of augmented reality and virtual reality studies in the field of sports and physical education using the Scopus database from 2019 to 2024. The analysis has focused on research productivity, document types, journal rankings, popular papers, commonly cited keywords, and co-authorship trends. Materials and methods. Bibliometric analysis was used as a research method for carrying out the study. Research stage (1) identified data using the Scopus database for the Boolean keywords "augmented reality" AND "virtual reality" AND "sports education" or "physical education". Stage (2) of the search considered original data from articles, conferences, and English language books. Stage (3), initial identification, yielded 1,174 documents, which were then filtered to produce 27 documents suitable for further inquiry. The techniques for collecting and analyzing data included using Mendeley, VosViewer, and Excel. Results. In 2022, research productivity increased rapidly, with the number of documents 8 (30%), the most common document type being original articles containing 19 documents (70%) falling into this category. The Scopus quartile 1 journal had the most articles with a total of 11 documents (41%), including Soltani and Morice's paper receiving 103 citations, while the trending keywords that appeared frequently were physical education and virtual reality. Regarding researchers who often engage in collaborative endeavours, it was found that there were 18 scientists working on the same topic. Conclusions. Based on these findings, research subjects on sports education using augmented and virtual reality are still needed to improve knowledge.